High‐temperature Raman spectroscopy of microstructure around the growing β‐BaB2O4 crystal in the BaO–B2O3–Na2O system. (1st April 2014) - Liu, Shanshan; Zhang, Guochun; Wan, Songming; Jiang, Xingxing; Wang, Yuanyuan; Lin, Zheshuai; Wu, Yicheng
<x xml:space="preserve">Abstract</x> High‐temperature Raman spectroscopy has been applied to study in situ the microstructure of the solution near the β‐BaB2O4 crystal–solution interface in the BaO–B2O3–Na2O growth system. A boundary layer near the crystal–solution interface was observed. In accordance with the high‐temperature Raman spectroscopy and first principles calculations, a boron–oxygen structural model is proposed to explain the microstructure of the solution and growth habit. The results show that the growth solution contains a special group, [BO2ØBOØB=O]3− (Ø = bridging oxygen), which transformed to the growth unit [B3O6]3− near the interface.